Hyperglycemia activates FGFR1 via TLR4/c-Src pathway to induce inflammatory cardiomyopathy in diabetes - Xiong Chen; Jinfu Qian; Shiqi Liang; Jianchang Qian; Wu Luo; Yujuan Shi; Hong Zhu; Xiang Hu; Gaojun Wu; Xiaokun Li; Guang Liang (Elsevier, 2024)
Protein tyrosine kinases (RTKs) modulate a wide range of pathophysiological events in several non-malignant disorders, including diabetic complications. To find new targets driving the development of diabetic cardiomyopathy (DCM), we profiled an RTKs phosphorylation array in diabetic mouse hearts and identified increased phosphorylated fibroblast growth factor receptor 1 (p-FGFR1) levels in cardiomyocytes, indicating that FGFR1 may contribute to the pathogenesis of DCM. Using primary cardiomyocytes and H9C2 cell lines, we discovered that high-concentration glucose (HG) transactivates FGFR1 kinase domain through toll-like receptor 4 (TLR4) and c-Src, independent of FGF ligands. Knocking down the levels of either TLR4 or c-Src prevents HG-activated FGFR1 in cardiomyocytes. RNA-sequencing analysis indicates that the elevated FGFR1 activity induces pro-inflammatory responses via MAPKs-NFκB signaling pathway in HG-challenged cardiomyocytes, which further results in fibrosis and hypertrophy. We then generated cardiomyocyte-specific FGFR1 knockout mice and showed that a lack of FGFR1 in cardiomyocytes prevents diabetes-induced cardiac inflammation and preserves cardiac function in mice. Pharmacological inhibition of FGFR1 by a selective inhibitor, AZD4547, also prevents cardiac inflammation, fibrosis, and dysfunction in both type 1 and type 2 diabetic mice. These studies have identified FGFR1 as a new player in driving DCM and support further testing of FGFR1 inhibitors for possible cardioprotective benefits.